Ensuring Justice in the Trend of Remote Working: Legal Challenges and Implications for Companies and Workers - Weny Almoravid Dungga; Ahmad, Ahmad; Karem Aboelazm, Karem Aboelazm; Dewi Mulyanti, Dewi Mulyanti; Novendri M. Nggilu, Novendri M. Nggilu (Jurnal IUS Kajian Hukum dan Keadilan, 2026)
This study examines the legal challenges of remote working in Indonesia, aiming to inform comprehensive, justice-based employment policies. Employing a normative juridical method with statutory, conceptual, and case-based approaches, including analysis of Indonesian court decisions, the research reveals that remote work faces structural injustice due to regulatory gaps. The Ma power Law (Law No. 13/2003) and Job Creation Law (Law No. 11/2020 jo. Law No. 6/2023) lack specific remote work provisions, while foundational Civil Code (Burgerlijk Wetboek/BW) principles governing employment contracts remain underutilized. This regulatory vacuum generates legal uncertainty that disproportionately affects vulnerable workers. Persistent gaps concern working hours, overtime, occupational health and safety, data protection, monitoring, employment agreements, social security, and cross-border taxation, leaving weak and unilateral corporate policies as the de facto framework. Comparative analysis of Russia, Spain, Turkey, and the Netherlands confirms that comprehensive legislation is both feasible and necessary. Grounded in justice theory, this study argues that regulating of remote work goes beyond administrative technicalities and forms part of the protection of fundamental constitutional rights. Consequently, Indonesia must enact dedicated legislation establishing minimum standards to ensure equitable protection, dignity, equality, and legal certainty for all workers in the digital era..